Association between daytime napping and stroke: A dose–response meta‐analysis. (18th April 2021) - Jin, Xiaolin; Chen, Hanze; Li, Yuru; Xu, Wenying; Chen, Xinxin; Tian, Li; Teng, Weiyu
Abstract: Daytime napping is common in many regions around the world and has been an important part of people's daily life. Daytime napping has attracted increasing attention in recent years. Thus, we conducted a meta‐analysis to evaluate the relationship between daytime napping and stroke, and help reduce the risk of stroke by improving living habits. The Embase, PubMed, Web of Science and PsycINFO databases were searched for cohort studies published before October 2020 and eight eligible studies with 524, 408 participants and 5, 875 stroke cases were included in the final analysis. The pooled relative risk (RR) of stroke was 1.47 (95% confidence interval [CI]: 1.24–1.74; p < .001) with significant heterogeneity ( I 2 = 58%, p for heterogeneity = 0.02). However, the heterogeneity decreased when the study in which adjusting for sleep duration and stratifying the results based on sleep duration was not performed was excluded (RR: 1.38; 95% CI: 1.19–1.60, I 2 = 44%, p for heterogeneity = 0.10). In dose–response analysis, the linear trend indicated that for every 10‐min increase in daytime napping, the risk of stroke increased by 3%. Further well‐designed large studies are needed to explore the effects of daytime napping on stroke and the underlying biological mechanisms.